Change in the health promoting lifestyle behaviour of Turkish University nursing students from beginning to end of nurse training - ALPAR, ŞULE (My University, 2008)
In light of developments in science and technology, content has been added to the nursing curriculum to support and improve students' healthy lifestyle behaviours. The aim of this study was to determine whether any difference was observed in the behaviour of nursing students. This longitudinal and descriptive study was conducted with 57 students during 2002-2006 academic years Marmara University, School of Nursing. The "health promotion lifestyle profile" developed in 1987 by Pender et al. was evaluated as to its validity and reliability in Turkey by the HPLP (healthy lifestyle behaviour scale) adapted by Esin. Percentage, variance analysis, Cronbach α coefficient and the t-test were used in the analysis of data. The findings indicated that healthy lifestyle behaviours of nursing students changed over time, from when they began and at the end of every year during their nurse training. © 2008 Elsevier Ltd. All rights reserved.
Keywords: Healthy lifestyle behaviour; Nurse education